Sympathetic Responses to Noxious Stimulation of Muscle and Skin - Burton, Alexander R.; Fazalbhoy, Azharuddin; Macefield, Vaughan G. (Frontiers in Neurology, 2016)
Acute pain triggers adaptive physiological responses that serve as protective mechanisms that prevent continuing damage to tissues and cause the individual to react to remove or escape the painful stimulus. However, an extension of the pain response beyond signalling tissue damage and healing, such as in chronic pain states, serves no particular biological function; it is maladaptive. The increasing number of chronic pain sufferers is concerning, and the associated disease burden is putting healthcare systems around the world under significant pressure. The incapacitating effects of long-lasting pain are not just psychological - reflexes driven by nociceptors during the establishment of chronic pain may cause serious physiological consequences on regulation of other body systems. The sympathetic nervous system is inherently involved in a host of physiological responses evoked by noxious stimulation. Experimental animal and human models demonstrate a diverse array of heterogeneous reactions to nociception. The purpose of this review is to understand how pain affects the sympathetic nervous system by investigating the reflex cardiovascular and neural responses to acute pain and the longer-lasting physiological responses to prolonged (tonic) pain. By observing the sympathetic responses to long-lasting pain we can begin to understand the physiological consequences of long-term pain on cardiovascular regulation.